Reisseronia annae sp. nov.—a new parthenogenetic bagworm moth from Poland (Lepidoptera, Psychidae) - Larysz, Adam (Zootaxa, 2017)
Reisseronia annae sp. nov. is described from the province of Upper Silesia in southern Poland. The species is similar to its parthenogenetic relatives Reisseronia imielinella Malkiewicz, Sobczyk & Larysz, 2013 and R. gertrudae Sieder, 1962. The diagnosis of other related congeneric species is provided. The habitat and life history is described.